Is there any difference between endometrial hyperplasia and endometrial carcinoma in terms of expression of TRPM2 and TRPM7 ion channels? - Yalcin, Emre; Pala, Sehmus; Atilgan, Remzi; Kuloglu, Tuncay; Onalan, Ebru; Artas, Gokhan; Buran, Ilay (Tubitak Scientific & Technological Research Council Turkey, 2019)
Background/aim: This study compared TRPM2 and TRPM7 ion channel gene expression and irnmunohistochemical staining in endometrial hyperplasia and endometrium adenocarcinoma. Materials and methods: Sections were taken from paraffin blocks of 120 patients who were divided into 6 groups as follows: G1 (n = 20), proliferative endometrium (PE); G2 (n = 20), EH without atypia; G3 (n = 20), EH with atypia; G4 (n = 20), stage 1A, grade 1 EC; G5 (n = 20), stage 1A, grade 2 EC; and G6 (n = 20), stage 1A, grade 3 EC. TRPM2 and TRPM7 genes were analyzed with qRT-PCR in paraffin-embedded tissue samples. Under light microscopy, TRPM2 and TRPM7 immunostaining scores of the samples taken from polylysine slides were evaluated. Results: Compared to G1, TRPM2 mRNA gene expression was significantly downregulated in G3 and G5. TRPM2 immunoreactivity scores were similar in all groups. TRPM7 mRNA gene expression was significantly downregulated in G2, G3, and G6 when compared to G1. TRPM7 immunoreactivity scores were similar in G1, G2, and G3, but significantly decreased in G4, G5, and G6. Conclusion: Reduction in TRPM7 ion channel activity may be a progression marker for endometrial hyperplasia regardless of the atypical criteria.
Keywords: TRPM2; TRPM7; endometrial hyperplasia; endometrioid adenocarcinoma